Speculative somatics - Maranan, Diego S (Technoetic arts : a journal of speculative research, 2015)
Based on a presentation at The Undivided Mind conference at Plymouth University, this article sketches out speculative applications of somatics, the first person, phenomenological study of sensation, perception and movement. I first introduce the subject of somatics through an experiential exercise for the reader before summarizing theoretical aspects of somatic study. Drawing from the literature in embodied cognition and from personal recollections of embodied experiences, I propose how somatic approaches could potentially be used in working with immigrant communities, living in outer space, and empathizing with non-human animals.